Psichologo-pedagogiceskij podchod k diagnostike i korrekcii sorevnovatel'noj nadeznosti v komandnych vidach sportivnych igr - Mitin, E. A. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The purpose of the research is to define the opportunities of the psycho-pedagogical correction of competitive reli-ability in command kinds of sports in natural conditions of trainings and competitions. As a result of the researches there is considered the psycho-pedagogical approach to the group correction of the competitive reliability, including the diagnostics of the potential opportunities of a team and the representation of an initial model on the basis of the display of the individual parameters of sportsmen, development of recommenda-tions on group correction of sports significant qualities as the modelling microcycles, current and operative control of the efficiency of the means and methods of the correcting microcycles. The experimental data have confirmed the perspectivity of such an approach for the increase of competitive reliability of a team.